Platelet factor XIII gene expression and embolic propensity in atrial fibrillation - Gosk-Bierska, Izabella; McBane, Robert D.; Wu, Yanhong; Mruk, Jozef; Tafur, Alfonso; McLeod, Thomas; Wysokinski, Waldemar E. (Thrombosis and Haemostasis, 2011)
Nearly 15% of patients with non-valvular atrial fibrillation (NVAF) have left atrial appendage thrombus (LAAT) by transesophageal echocardiography (TEE) and yet the annual stroke rate averages 5%. The aim of this study was to identify variables influencing embolic propensity of LAAT. Platelet RNA was extracted from platelet-rich regions within formalin- fixed, paraffin-embedded specimens obtained from NVAF patients during cardiac surgery (26 LAAT from 23 patients) or peripheral embolectomy (51 thrombi from 41 patients). Platelet RNA was also assessed from whole blood from 40 NVAF patients. Expression of six platelet- predominate genes: H2A histone family, A1 domain of factor XIII, integrin α2bβ3; glycoprotein IX, platelet factor 4, glycoprotein Ib, was performed using TaqMan MGB-probe based quantitative real-time polymerase chain reaction. Platelet factor XIII subunit A gene expression was significantly lower in embolised compared to non-embolised thrombi as determined by normalised cycle threshold values (4.0 ± 1.2 v 2.8 ± 1.8, p=0.02). Expression of other genes did not differ by embolic status. In conclusion, RNA extracted from formalin-fixed, paraffin-embedded platelet-rich tissues can be used for analysis of platelet- predominate gene expression. Variable factor XIII gene expression in thrombi generated during NVAF may in part explain the propensity to embolisation.
Keywords: Atrial fibrillation; left atrium appendage thrombus; platelets; FXIII; stroke